Ethiopia, Europe and Modernity: A Preliminary Sketch - Crummey, Donald (Aethiopica, 2000)
This paper explores some of the issues of cultural epistemology which underlie the relations between Ethiopia and Europe. It briefly explores the origins of modern diplomatic contacts, arguing that the appropriation of modernity increasingly became a central concern of Ethiopia’s rulers in their relations with Europe. It then raises the question, if Europeanized modernity has increasingly marked Ethiopia in the twentieth century, how are we to discern Ethiopia’s contribution to this process? To what extent, in its modernization, has Ethiopia’s educated elite lost contact with an indigenous point of view? The paper argues that a critical appreciation of modernity in Ethiopia must be made against a background which historicizes the process whereby it came about, which takes fully into account the modes of reasoning embodied in Gǝʿǝz texts, and which privileges the views of those rural Ethiopians so lightly touched by modernity.